Transformation of Criminal Law in Indonesia: An Analysis of Social Rights Protection through a Qualitative Descriptive Approach - Tasya Nabilla; Benny Djaja; Maman Sudirman (Jurnal Indonesia Sosial Sains, 2024)
This research aims to analyze the protection of human rights in criminal law in Indonesia, considering the importance of integrating human rights protection into a fair and effective criminal law system. This study uses a qualitative descriptive research method, utilizing primary data from case studies related to human rights violations and secondary data in the form of scientific literature, laws, and official documents from related institutions. Data were collected through documentation study techniques and media content analysis, which allowed for in-depth exploration of various cases and legal policies that had been implemented. Content analysis was used to identify key themes in legal documents and literature studies, while theoretical modeling helped formulate a theoretical model that links criminal law to human rights protection. The results of the study indicate that there is a discrepancy in several implementations of criminal law with human rights principles, especially in terms of protecting victims and fulfilling the rights of the accused. The conclusions obtained highlight the need for criminal law reform to ensure the fulfillment of basic rights for all individuals in accordance with international standards. This study provides recommendations for policymakers to integrate human rights protection more systematically into the criminal law system in Indonesia.